A cross-lagged model of the relationship between violent video game exposure and moral disengagement in middle school and high school students. (October 2017) - Teng, Zhaojun; Nie, Qian; Pan, Yangu; Liu, Yanling; Guo, Cheng
Abstract: Previous studies have proved that violent video game exposure might have an association with moral disengagement; however, the directionality of this correlation remains unclear. Therefore, we examined the reciprocal effects between violent video game exposure and moral disengagement in a longitudinal study. The sample included 1393 adolescents (48.7% boys) in the seventh (middle school students, n  = 694, M age  = 13.15 years) and tenth (high school students, n  = 699, M age  = 15.93 years) grades at six Chinese secondary schools. The results showed that high school students' levels of moral disengagement were higher than those of middle school students, and violent video game exposure was positively associated with moral disengagement. The cross-lagged panel model suggested that violent video game exposure predicted moral disengagement (six months later) in all participants, with a slightly stronger effect in middle school students. The finding also indicated differences in the development of perspective regarding the association between violent video game exposure and moral disengagement, which observed a predictive effect for middle school students but a lagged effect for high school students. Thus, different preventions and interventions should be distinguished for middle school and high school students. Highlights: Moral disengagement levels were higher in high school students. Violent video game exposure was positively associated with moral disengagement. The predictive effect of violent video games was stronger in middle school students.